Efektivitas Media Digital Dalam Meningkatkan Motivasi Belajar Pendidikan Agama Islam - Berliandra Agasa (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the effectiveness of digital media in enhancing students’ learning motivation in Islamic Religious Education. The research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The research subjects consisted of an experimental group taught using digital media and a control group taught through conventional methods. Data were collected using a learning motivation questionnaire that had been tested for validity and reliability. Data analysis was conducted using descriptive and inferential statistics. The results indicate that students who learned through digital media demonstrated significantly higher learning motivation compared to those who learned without digital media. These findings suggest that digital media is an effective innovative learning strategy in Islamic Religious Education to improve students’ learning motivation. Therefore, the pedagogical integration of digital media is recommended to support more engaging and meaningful Islamic education learning.